The Use of PowerPoint Slide Media to Improve Student Learning Outcome In Mathematics Learning - Hery Kresnadi (Universitas Tanjungpura, 2021)
Generally, this study aims to describe the improvement of learning outcome using PowerPoint slide media on arithmetic learning in fourth-grade elementary school students. The method used was descriptive in Classroom Action Research (CAR). This study was done in three cycles and found the description about a learning plan, learning implementation, characteristic of PowerPoint slide media, implementation technique of learning evaluation, and improvement of student learning outcomes. There is an improvement of learning in every cycle. The student reaching the target of learning (KKM) was increased from 37% in cycle 1 up to 68% in cycle 3.